Nanodiamonds: Selective Antimicrobial and Antibiofilm Disrupting Properties of Functionalized Diamond Nanoparticles Against Escherichia coli and Staphylococcus aureus (Part. Part. Syst. Charact. 8/2015). (August 2015) - Khanal, Manakamana; Raks, Viktoria; Issa, Rahaf; Chernyshenko, Volodymyr; Barras, Alexandre; Garcia Fernandez, Jose M.; Mikhalovska, Lyuba I.; Turcheniuk, Volodymyr; Zaitsev, Vladimir; Boukherroub, Rabah; Siriwardena, Aloysius; Cooper, Ian R.; et al.
<x xml:space="preserve">Abstract</x> The antibacterial and antibiofilm properties of diamond nanoparticles are shown by A. Siriwardena, P. J. Cragg, S. Szunerits, and co‐workers to be both bacterium‐ and ligand‐dependent. On page 822, S. aureus‐induced biofilm inhibition is observed for ND‐NH2, ND‐COOH, and ND‐OH particles, but proves only moderate even at the highest particle concentrations tested. ND‐NH2 and ND‐COOH, however, are found to inhibit E. coli‐induced biofilm formation at levels comparable to the known E. coli biofilm disruptor, ampicillin.